The Role of Attributes Organizational Commitment as mediators Between Work-Life Balance on Employee Performance - Gede Ariadi; Agisius Wandra (Universitas Hayam Wuruk Perbanas, 2024)
Work-life balance contributes to a healthy, satisfying, and successful life. An imbalance in work-life dynamics can negatively impact both employee performance and their personal lives. This study employs exchange relationship theory to explore organizational commitment as a mediating variable, which includes affective commitment, continuance commitment, and normative commitment, in the relationship between work-life balance and employee performance. The research focuses on employees of micro, small, and medium enterprises (MSMEs) in Salatiga Regency. Data were collected through questionnaires distributed to 111 respondents, and the analysis was conducted using structural equation modeling. The findings reveal that affective and continuance commitments are crucial in linking work-life balance to employee performance. In contrast, normative commitment does not significantly influence this relationship. Theoretically, social exchange theory highlights that continuance commitment is a key mediator in the connection between work-life balance and employee performance.